If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 16) = (x + 14) Reorder the terms: (16 + 2x) = (x + 14) Remove parenthesis around (16 + 2x) 16 + 2x = (x + 14) Reorder the terms: 16 + 2x = (14 + x) Remove parenthesis around (14 + x) 16 + 2x = 14 + x Solving 16 + 2x = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + 2x + -1x = 14 + x + -1x Combine like terms: 2x + -1x = 1x 16 + 1x = 14 + x + -1x Combine like terms: x + -1x = 0 16 + 1x = 14 + 0 16 + 1x = 14 Add '-16' to each side of the equation. 16 + -16 + 1x = 14 + -16 Combine like terms: 16 + -16 = 0 0 + 1x = 14 + -16 1x = 14 + -16 Combine like terms: 14 + -16 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| (n^5)^4/5 | | 1.03x=113740 | | 4x+18=2x+54 | | 103x=113740 | | 7/11x=2 | | 3x+24y=12 | | X^2-8x=32 | | 28-2x=13-7x | | 3+30x=15x+21 | | 13+3(3x+8)=8-x | | 2ln(3x-2)+2=0 | | 6z+z=z-4 | | .50x+0.15(30)=27.5 | | 11-14x+28+30x=4x-12+23+6x | | 3x+6=-50-5x | | 36-6x=8-10x | | (1/2x-2)^5 | | 1+9x=-23+x | | 9x(x-2)=4(x+2) | | 2x+24=3+8x-9 | | 10a-50-28(a-2)=14(3a+15) | | 4464=10(p+48) | | 4ln(6x)=2 | | 4+5x=6x+1 | | 11x-1=10x+2 | | 3x=5b | | p=90x-200-x^2 | | 8m^3-24m^2+18m=0 | | 4/16=B | | p=25-0.01s^2 | | (sqrt)3x-2=5 | | 7.3+2.6x= |